A new post-Liangzhu Lower Yangtze culture: the Early Bronze Age Tiaotou and Pishan sites. (April 2023) - Allen, Edward; Yang, Jindong; Lin, Sen; Zhou, Yijing; Sheng, Pengfei
Abstract: Abstract : Excavations at Tiaotou reveal evidence for cultural continuity through the late third to the mid first millennia BC. This research explores shifts in subsistence, production and ritual at Tiaotou, and the emergence of the Pishan-Tiaotou Culture (1200–1000 BC). Tiaotou/Pishan-Tiaotou represents a missing link among Taihu Lake archaeological cultures and contributes to our knowledge of complex political formations and cultural change in Bronze Age southern China.